Zakat Produktif untuk Peningkatan Pendapatan Masyarakat Miskin - Syamsuri, Syamsuri; Utami, Alfiya (Innovative: Journal Of Social Science Research, 2024)
This research examines the role of productive zakat in increasing the income of poor communities using a descriptive qualitative method and a literature review approach. Productive zakat, distinct from consumptive zakat, focuses on providing funds used for business capital, skills training, and economic development to empower zakat recipients. The study aims to identify and analyze how productive zakat can reduce poverty and improve the welfare of impoverished communities. Through a literature review, this research explores various studies, reports, and data related to the implementation of productive zakat in different regions and its impact on income improvement. The findings show that productive zakat can significantly improve the economic conditions of the poor by giving them opportunities to start businesses and enhance their skills. However, to achieve optimal results, effective management, transparency, and cooperation between zakat institutions, the government, and the community are required. This study provides recommendations to improve the implementation of productive zakat as a strategy for poverty alleviation and enhancing social welfare.Keyword: income, poor communities, productive zakat